CD-1 mice females recognize male reproductive success via volatile organic compounds in urine - A. S. Khotskina; E. L. Zavjalov; E. P. Shnayder; L. A. Gerlinskaya; S. O. Maslennikova; D. V. Petrovskii; M. N. Baldin; A. L. Makas; V. M. Gruznov; M. L. Troshkov; M. P. Moshkin (Вавиловский журнал генетики и селекции, 2023)
Sexual selection is considered as one of the leading factors of evolutionary development. In the conditions of incessant competition, specialized methods of attracting individuals of the opposite sex as well as criteria for assessing the quality of a sexual partner have been formed. In order for animals to rely on signaling from sexual partners, the signal must reflect the morpho-physiological status of animals. A high reproductive efficiency of male mice is a good advantage for mate selection and thus must be somehow demonstrated to potential mates. The aim of our study was to find out if male mice could demonstrate their reproductive efficiency through urine volatile organic compounds. The experiment implies cohabiting one male with two mature females for 6 days. The reproductive success of the male was assessed by the presence or absence of pregnant females. At the same time, naive females, who did not participate in reproduction, assessed the urine of the successful males as more attractive, which was expressed in shorter Latency time of sniffs in the Olfactory test. Using a rapid headspace GC/MS analysis, we have found volatile organic compounds (VOCs) in male urine that correlated with female behavior. It turned out that these substances are derivatives of mouse pheromone 6-hydroxy-6-methyl-3-heptanone. The amplitude of peaks corresponding to this pheromone correlated with the testosterone level in blood and the weight of preputial glands. The amplitude of peaks increased in males after mating with whom the females turned out to be pregnant. It is important to note that body weight, weight of testes, weight of seminal vesicles, weight of preputial glands, and plasma testosterone level alone are not reliable indicators of male reproductive success. Thus, the content of the pheromone 6-hydroxy-6-methyl-3-heptanone in the urine of males can serve as a good predictor of the quality of the male as a sexual partner for female CD-1 mice.